Bagaimana Menjadi Garam dan Terang Melalui Media Sosial? - Victor Christianto (CARAKA: Jurnal Teologi Biblika dan Praktika, 2020)
Abstract. For those of us born before the 90s, we may often see millennials or Z generations or alpha generations as a group of young people who are less concerned about the environment, absorb themselves because they are too busy with devices and so on. Maybe this is true, because those who were born after the 1990s from childhood have become accustomed to PCs, laptops or devices owned by parents, so the devices have become an extension of their hands. This is certainly not healthy, but also a challenge for us: how to convey the truth of the Good News and especially to be salt and light to that generation? Through this article the author wants to convey how to teach the truth to millennials so that our generation is not lost from contact with them over the times.Abstrak. Bagi kita yang dilahirkan sebelum tahun 90an, mungkin sering melihat generasi milenial atau generasi Z atau generasi alpha sebagai sekumpulan anak-anak muda yang kurang peduli lingkungan, asyik sendiri karena terlalu sibuk dengan gawai dst. Mungkin hal tersebut ada benarnya, karena mereka yang lahir setelah tahun 1990an dari kecil sudah terbiasa dengan PC, laptop atau gawai milik orangtua, sehingga gawai telah menjadi kepanjangan tangan mereka. Ini tentu tidak sehat, namun juga suatu tantangan bagi kita: bagaimana menyampaikan kebenaran Kabar Baik dan terutama menjadi garam dan terang kepada generasi tersebut? Melalui artikel ini penulis ingin menyampaikan bagaimana mengajarkan kebenaran kepada generasi milenial sehingga generasi kita tidak terhilang seiring perkembangan zaman.